Enhancing Employer Brand Hotel Industry Through Knowledge-Based Recruitment and Employee Value Propositions - Darawanti, Tri; Silitonga, Parlagutan; Raharjo, Pamuji (Universitas Bina Sarana Informatika, 2023)
This study investigates the role of knowledge-based recruitment, a component of knowledge-based human resource management (K-B HRM), in mediating the relationship between the value proposition of key employees and employer branding. This research uses the PLS-SEM method and purposive sampling to survey employees working in 3- to 5-star hotels in West Java and Jakarta. The results reveal that the value proposition of key employees has a positive and significant impact on both knowledge-based recruitment and employer branding. However, it is observed that knowledge-based recruitment only has a positive but insignificant effect on employer brand, indicating that it does not significantly mediate the relationship between key employees' value proposition and employer branding. These findings offer valuable insights to hotel companies in their efforts to enhance their reputation and image as sought-after workplaces for top talent within the hotel industry. Furthermore, these findings support the Indonesian government's initiatives to foster the development of human resources in the tourism sector. By strategically optimizing key employees' value propositions and diligently implementing knowledge-based recruitment practices, hotel companies have the remarkable opportunity to enhance their employer brand significantly.